(3JUGfja CHj HcQ CMeO Hf Ydi Hf KGHJ GdWHjH GdHZOGOis - (3CHi HcQ CMeO Hf Ydj Hf KGHJ GdNWjHs; (3GdNWjH GdHZOGOj , CHh HcQ CMeO Hf Ydj Hf KGHJ GdNWjH GdHZOGOj,J (B463 (3g` s ((3eMeO UGOb Hf GdSjO Cejf GdeGY s)
(3ChdgG (B:s
(3cJGH JGQjN eOjfI GdSdGe hCNHGQ eMOKjgG s
(3BNQgG (B:s
(3hcGf jPgH Edi ePgH CHj GdMSf GdCTYQi ai GdCUhd Ufa bHd ehJg ef GdcJH eG cJHfGg Yfg ced GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdNGeSs
(3GfXQg eY GdeNWhW Qbe (B183s
(3HgG fXGe GdJYbjHIs
(3gPg GdJUGfja Edi SfI (B453s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B172 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B3s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs